Quality of care and user satisfaction in an Emergency Service of a Social Security Hospital - Arce Huamani, Miguel Angel (2024)
Introduction: The quality of care and user satisfaction in an emergency service has become a priority concern for patients. Especially since the health system does not supply enough to public establishments to provide quality care and obtain user satisfaction. Objective: Establish the relationship between the quality of care and user satisfaction in an Emergency Service of a Social Security Hospital. Methodology: A cross-sectional analytical study was carried out with a sample of 400 patients in a Social Security Emergency Service in the southern region of Peru; The SERVPERF questionnaire and the one elaborated by Feletti G, Firman D and Sansón-Fisher R were used as instruments to measure the variables. The data was presented using tables and graphs. Results: The dimensions of the quality of care such as reliability, responsiveness, security, empathy, and tangible aspects, it was found that 49.25%, 67%, 72.25%, 54.25% and 55.75% agreed with the care provided, respectively. In the user satisfaction variable, 50.25% of users agreed. On the other hand, the relationship between the variables using Spearman's Rho was 0.8590 with a p<0.05, it is statistically significant. Conclusions: It was found that there is a moderate and statistically significant positive relationship between the quality of care and user satisfaction. Keywords: Quality of Health Care, Patient Satisfaction, Emergency Service, Hospital (Source: MeSH NLM).